2018
DOI: 10.3390/catal8030120
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Asymmetric Catalysis and Chromatographic Separation by Chiral Metal–Organic Frameworks

Abstract: Metal-organic frameworks (MOFs), as a new class of porous solid materials, have emerged and their study has established itself very quickly into a productive research field. This short review recaps the recent advancement of chiral MOFs. Here, we present simple, well-ordered instances to classify the mode of synthesis of chiral MOFs, and later demonstrate the potential applications of chiral MOFs in heterogeneous asymmetric catalysis and enantioselective separation. The asymmetric catalysis sections are subdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 120 publications
0
40
0
Order By: Relevance
“…Chiral molecules, such as protein, nucleic acid, and ribonucleic acid, are the basic ingredients in living systems, which are almost composed of elementary entity with single optical activity, and play a critical role in the physiological process . Simultaneously, these chiral molecules have been widely used in various areas of asymmetric synthesis, chiral recognition, enantioseparation, etc . Particularly, materials showing polarized light are potentially useful in liquid crystal display panel, 3D imaging systems, information storage, nonlinear optics, spintronics devices, and biological probes …”
Section: Introductionmentioning
confidence: 99%
“…Chiral molecules, such as protein, nucleic acid, and ribonucleic acid, are the basic ingredients in living systems, which are almost composed of elementary entity with single optical activity, and play a critical role in the physiological process . Simultaneously, these chiral molecules have been widely used in various areas of asymmetric synthesis, chiral recognition, enantioseparation, etc . Particularly, materials showing polarized light are potentially useful in liquid crystal display panel, 3D imaging systems, information storage, nonlinear optics, spintronics devices, and biological probes …”
Section: Introductionmentioning
confidence: 99%
“…Easy linkage of MOFs to silica and other composites, including their incorporation in monoliths, also favor the applicability of MOFs in LC stationary phases. Furthermore, MOFs designed to present a specific and unique chiral center type are quite attractive to perform chiral separations [100], of the utmost importance in pharmaceutical, industrial and biomedicine applications. In any case, the incorporation of MOFs as stationary phases in GC and LC, or as pseudo-stationary phases in capillary electro-chromatography (CEC), benefits from the low numbers of MOFs required in such phases, together with the clear reutilization of such phases.…”
Section: Mofs In Chromatographymentioning
confidence: 99%
“…Porous metal‐organic coordination polymer (PCP), which is constructed from the self‐assembly of organic ligands with metal ions or metal clusters, has emerged as one of potential porous materials in separations and purifications, due to their unique properties of controllable synthesis, structural diversity, fine‐tuned porosity, etc . In particular, remarkable progress on the PCP‐based HPLC separations has also been made . Thereinto, the number of such CSPs based on chiral PCPs is relatively limited compared with achiral ones Up to date, most reported CSPs based on PCPs for HPLC separation were only able to be used to separate one or two kinds of enantiomers with appropriate resolution ( R s > 1.5) and decent selectivity factor (α) .…”
mentioning
confidence: 99%
“…In particular, remarkable progress on the PCP‐based HPLC separations has also been made . Thereinto, the number of such CSPs based on chiral PCPs is relatively limited compared with achiral ones Up to date, most reported CSPs based on PCPs for HPLC separation were only able to be used to separate one or two kinds of enantiomers with appropriate resolution ( R s > 1.5) and decent selectivity factor (α) . However, these previous studies have shown that the separation of enantiomers is mainly caused by different interactions between the PCPs and the resolved molecules, and low column efficiency will be involved when the resolved molecules could not enter the small pores .…”
mentioning
confidence: 99%